Colorimetric biosensing of triglyceride in waste water using lipase immobilized ZnO nanoparticle enriched chitosan nanoconjugate - Shambhavi; Mahadevan B. Iyer; Soham Chattopadhyay; Debasmita Mondal (Journal of Taibah University for Science)
We constructed a liquid-phase colorimetric biosensor to detect Triglycerides (TG) contamination in water using a Porcine Pancreatic Lipase Immobilized Zinc – chitosan nanocomposite matrix with Phenolsulfonphthalein as the chromophore. The nanoparticle-augmented matrix was characterized using an SEM—the change in the chromophore colour from red to yellow indicated vegetable oil hydrolysis and fatty acid release. The biosensor showed a LOQ between 25–500 µg/mL at an operating temperature between 25–45 °C, over a pH range of 4–9 within 5 minutes. The biosensor showed resilience to samples contaminated up to 50 times the BIS permissible limits for iron, copper and manganese. The sensor showed repeatability of nearly 100% with the LOD 3 µg/mL, sensitivity 47.1 U/µg/cm2 and retained up to 80% of its activity till the 10th day when stored at 10 °C. A fully adept version of the biosensor can be applied to detect TG in water and wastewater.